Duty and dilemma: Perioperative nurses hiding an objection to participate in organ procurement surgery - Smith, Zaneta (Wiley-Blackwell Publishing Ltd., 2017)
Perioperative nurses assist in organ procurement surgery; however, there is a dearth of information of how they encounter making conscientious objection requests or refusals to participate in organ procurement surgery. Organ procurement surgical procedures can present to the operating room ad hoc and can catch a nurse who may not desire to participate by surprise with little opportunity to refuse as a result of staffing, skill mix or organizational work demands. This paper that stems from a larger doctoral research study exploring the experiences of perioperative nurses participating in multi-organ procurement surgery used a grounded theory method to develop a substantive theory of the nurses’ experiences. This current paper aimed to highlight the experiences of perioperative nurses when confronted with expressing a conscientious objection towards their participation in these procedures. A number of organizational and cultural barriers within the healthcare organization were seen to hamper their ability in expressing a conscience-based refusal, which lead to their reluctant participation. Perioperative nurses must feel safe to express a conscientious objection towards these types of surgical procedures and feel supported in doing so by their respective hospital organizations and not be forced to participate unwillingly.